2016
DOI: 10.1515/pjst-2016-0007
|View full text |Cite
|
Sign up to set email alerts
|

Sport and Tourism Between Modernity and Postmodernity

Abstract: The text presents and analyses manifestations of modernity and postmodernity in the field of competitive and recreational sport, physical education, leisure, and tourism. The paper builds upon an extensive literature survey and presents the concept and key features of postmodern societies and the modernity-postmodernity debate in sports with reference to postmodern tendencies in tourism. We have attempted to determine the proportions of tradition, modernity, and postmodernity in contemporary sport and tourism,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…By extension, it can be suggested that postmodern athletes might find diversification more rewarding than specialization. Lenartowicz, Isidori, and Maussier (2016) considered sport tourism and serious leisure in the context of postmodernism, arguing that " … the key elements of leisure sport are mostly postmodern and focused on the notion of individualization and freedom expressed especially in alternative sports … " (p. 65) as opposed to commercialized professional sports and mega-sport events. In this light, serious sport tourists develop careers and seek both quality experiences and the value added by "relational capital" (p. 67).…”
Section: Serious Leisure and Social Worldsmentioning
confidence: 99%
“…By extension, it can be suggested that postmodern athletes might find diversification more rewarding than specialization. Lenartowicz, Isidori, and Maussier (2016) considered sport tourism and serious leisure in the context of postmodernism, arguing that " … the key elements of leisure sport are mostly postmodern and focused on the notion of individualization and freedom expressed especially in alternative sports … " (p. 65) as opposed to commercialized professional sports and mega-sport events. In this light, serious sport tourists develop careers and seek both quality experiences and the value added by "relational capital" (p. 67).…”
Section: Serious Leisure and Social Worldsmentioning
confidence: 99%
“…The facilities and infrastructure are still not optimal. They need to be improved first..." (B1, [4][5][6][7][8][9][10][11][12] "The development of facilities and infrastructure is the most important and necessary" (B2, [4][5][6][7][8][9][10][11].…”
Section: " Resources Must Be Considered If Development Is To Take Pla...mentioning
confidence: 99%
“…"... The most dominant effort is to improve the quality of supporting infrastructure, given the location of traditional sports on islands (A5, [3][4][5][6][7][8][9][10][11][12][13].…”
Section: Infrastructurementioning
confidence: 99%
See 1 more Smart Citation
“…Leisure time belongs to important factors determining the purchasing power and the consumption behavior of a household, and thus the size and structure of consumption. Increasing importance is attached to both its resources and to the attractiveness and quality of its management [1,2]. In order to rest and entertain in free time, recreation and culture are used.…”
Section: Introductionmentioning
confidence: 99%